New Directions in Theorizing Qualitative Research : Theory As Resistance - Denzin, Norman K. (Myers Education Press, 2020)
What can it mean to resist in these troubled times, and how can we do so through theory? This volume presents novel ideas on how to accomplish this in the context of the field of qualitative research. The authors show us how we might go beyond pre-existing, systematized research methodologies to find our way. They challenge us to go beyond facile modes of thought and slow down any mechanistic practices of research, a slowing that can be surprisingly generative regarding pedagogy and knowledge production. The articles think through theories such as ones theorizing the postcolonial for the purpose of responding to global hegemony regarding institutional experiences of academe. They engage with practices of new materialism and show the multiform ways in which theory can be a companion to us in our journey of research. Further, the articles question hold-overs from humanist and modernist thought so that we might perform an inclusive pedagogy. Rather than falling into the cynical view that the world is too troubled to change, this volume presents a sound vision that we have no option but to engage in theoretical practice, for now, there's no time not to think.
Keywords: Qualitative research.; Recherche qualitative.; Qualitative research